Analysis of the level of Vegetation Density in the City of Ambon Based on NDVI Using Landsat 8 OLI Imagery - Silooy, Lisa C; Siahaya, Willem A; Haumahu, Johanes P (JURNAL BUDIDAYA PERTANIAN, 2023)
Vegetation can be interpreted as a combination of several plants with different types living together in a place that forms a unit that interacts with each other, both among individuals from the plants themselves and the interaction of environmental factors. Vegetation density is the percentage of a group of plants or vegetation that live in an area. Vegetation index transformation (NDVI) is one of the data processing techniques to determine vegetation density. This study aims to determine the level of vegetation density in Ambon City using the NDVI Landsat 8 OLI imagery transformation. The method used in this research was the Normalized Difference Vegetation Index (NDVI) transformation of Landsat 8 OLI imagery. Based on the results of the study, there were five levels of vegetation density, namely: non-vegetation with a value of -0.6320-0.3660, a very low-density level with a value of 0.3661-0.5562, a low-density level with a value of 0.5563-0.7464, medium density level with value of 0.7465-0.8732 and a high-density level with value of 0.8733-1.00000. The land covers found were built-up areas, shrubs, mixed plantations, mixed crops, and secondary dryland forests. The non-vegetation class has an area of 761.95 ha (2.37%), the very low-density level has an area of 1234 ha (3.83%), the low-density level has an area of 2333.87 ha (7.25%), the medium density level has an area 3689.10 (11.45%), and the high-density level has an area 24194.29 ha (75.10%). The accuracy of the analysis of the research was a very good category because the Kappa value was 91% and overall accuracy was 93%.